Deleterious effects of purulent sputum sol on human ciliary function in vitro: at least two factors identified. Issue 4 (April 1987) - Sykes, D A; Wilson, R; Greenstone, M; Currie, D C; Steinfort, C; Cole, P J
Abstract : Patients with chronic bronchial sepsis have impaired mucociliary clearance. A study was carried out on the effect of sputum sol (obtained by rapid centrifugation of purulent sputum) from 20 patients with chronic bronchial sepsis on the beating of human nasal cilia in vitro by a photometric technique. Thirteen sols caused significant (p less than 0.001) ciliary slowing. Two patterns of slowing were observed: firstly, a gradual onset associated with epithelial disruption (inhibited by alpha 1 antiprotease) and, secondly, an immediate onset associated with ciliary dyskinesia and ciliostasis (inhibited by chloroform extraction). The ciliary slowing activity of sputum sols was associated with the isolation of Pseudomonas aeruginosa (p less than 0.01). It is concluded that purulent sputum contains at least two factors that impair ciliary beating--one a serine protease, which is probably a product released by the host's phagocytic defences, and the other, which is chloroform extractable and probably a bacterial product.